Hubungan Penggunaan Gawai dengan Kejadian Sindroma Mata Kering pada Mahasiswa - Assa, Ishak A.; Wungouw, Herlina I.; Pangemanan, Damajanty H. (Universitas Sam Ratulangi, 2025)
Abstract: Gadgets have become a fundamental necessity in contemporary human life, especially for students to aid in their educational process. Uncontrolled gadget usage can lead to detrimental health effects, particularly in the eyes, such as decreased blinking reflex, resulting in increased evaporation and dry eye syndrome. This study aimed to evaluate the relationship between gadget usage and dry eye syndrome among students. This was an analytical and observational with a cross-sectional design, using simple random sampling. Samples were 193 students of the Department of Informatics Engineering, Faculty of Engineering, Universitas Sam Ratulangi. Data were analyzed using the Spearman correlation test with a significance level of 0.05. The results showed that of the three categories, there were only respondents with high gadget usage (22.8%) and moderate gadget usage (77.2%). Based on OSDI, 5.2% of respondents were categorized as moderate and 94.8% as poor. The Spearman correlation test obtained a p-value of 0.011 (<0.05) and r = 0.182, indicating a significant relationship between gadget usage and dry eye syndrome with a positive and very weak correlation. In conclusion, there is a significant correlation between gadget usage and the incidence of dry eye syndrome among students at the Faculty of Engineering, Department of Informatics Engineering at Universitas Sam Ratulangi. The higher the gadget usage, the higher the risk of dry eye syndrome. Keywords: gadget usage; dry eye syndrome Abstrak: Gawai menjadi salah satu kebutuhan dasar dalam kehidupan manusia saat ini, terlebih bagi mahasiswa untuk membantu proses pendidikan. Penggunaan gawai yang tidak terkontrol dapat menimbulkan efek berbahaya bagi kesehatan, salah satunya pada mata, yaitu terjadinya penurunan refleks berkedip yang mengakibatkan peningkatan evaporasi pada mata sehingga terjadi mata kering. Penelitian ini bertujuan untuk mengevaluasi hubungan antara penggunaan gawai dengan kejadian sindroma mata kering pada mahasiswa. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Teknik pengambilan sampel yakni simple random sampling. Sampel penelitian ini ialah 193 mahasiswa Fakultas Teknik Jurusan Teknik Informatika Universitas Sam Ratulangi. Data dianalisis menggunakan uji korelasi Spearman. Hasil penelitian mendapatkan bahwa dari ketiga kriteria penilaian, hanya didapatkan responden dengan penggunaan gawai tinggi (22,8%) dan penggunaan gawai sedang (77,2%). Berdasarkan kategori OSDI didapatkan responden dengan kategori sedang (5,2%) dan kategori berat (94,8%). Hasil uji korelasi Spearman dengan perolehan nilai p sebesar 0,011 (p<0,05) menunjukkan adanya hubungan bermakna antara penggunaan gawai dan sindroma mata kering. Nilai koefisien 0,182 menunjukkan korelasi yang sangat lemah dan searah. Simpulan penelitian ini ialah terdapat hubungan bermakna antara penggunaan gawai dengan kejadian sindroma mata kering pada mahasiswa Fakultas Teknik Jurusan Teknik Informatika Universitas Sam Ratulangi. Semakin tinggi penggunaan gawai, semakin tinggi kejadian sindroma mata kering. Kata kunci: penggunaan gawai; sindroma mata kering